SOBRE A FORMAÇÃO DE PROFESSORES EM MODELAGEM MATEMÁTICA NA EDUCAÇÃO MATEMÁTICA: DO ÔNTICO AO ONTOLÓGICO. - Loureiro, Daniel Zampieri (2022)
Teacher training has gained focus in the academic scenario, unfolding under a variety of areas of interest, including Mathematical Modeling in Mathematics Education. However, even with a diversity of themes being explored in this soil, it is still possible to notice the absence of works that speak of the understanding of what is the training in Modeling by those who are dedicated to them. With this, we have as an investigative guide the question: “What is this, the training of teachers in Mathematical Modeling in Mathematics Education according to researchers who are dedicated to it?” Directed by that questioning and assuming a phenomenological posture of investigation, proceeded to the survey of significant subjects for research based on previously established criteria. After the possible reductions, moved on to seven subjects considered significant, whose interviews were carried out and later transcribed. The readings of the transcript of the interviews and the highlighting of the units of meaning were carried out with the aid of the Software Atlas t.i. units that after careful and careful reading culminated in the categories a) Expression of the Trainers' Experience / Experience / Practice in/with Modeling b) Expression of the trainers' theoretical beliefs in Mathematical Modeling c) Expressions of theoretical beliefs, ways of doing about Training / Education / Teacher. The hermeneutic movement employed, guided by questioning, allowed us to bring to light the perceptions of the significant subjects of research that revealed senses and meanings attributed to an encounter with Modeling, which opened up in reflections that say about those who implement, think and does Modeling, with a when to do it, as well as a how to do Modeling. The comprehensive horizon that is revealed from the analyzes employed allows us to infer that the subjects make a movement of realizing, which concerns, among other aspects, a search linked to the knowledge produced and/or new knowledge related to the Training of Teachers in Modeling Math; a mediator that also says, both about knowledge and about the subject who produces or disseminates it.